2020
DOI: 10.1177/0095798420976054
|View full text |Cite
|
Sign up to set email alerts
|

How Variations in Behavior and Phenotype Affect In-Group Stereotyping and Belonging Among African American Adolescents and Emerging Adults

Abstract: The present study based on social identity theory and phenotypic bias models examined how variations in phenotype and behavior related to in-group belonging and stereotyping for African American adolescents and emerging adults. Although ethnic-racial typicality is often considered as either phenotypic or behavioral, little research has investigated the interaction of these two dimensions. Forty African American high school students ( Mage = 15.38, SD = 0.81) and 42 college students ( Mage = 19.55, SD = 1.35) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Previous research has found that those who appear more typical of their ingroup are more likely to experience outgroup discrimination (Maddox, 2004) and are perceived as more likely to be accepted among their ingroup (Wilson, 2021). Furthermore, previous studies have indicated that felt typicality among ethnic-racial minoritized persons was positively related to self-esteem and well-being (Hoffmann et al, 2020;Mitchell et al, 2018;Wilson & Leaper, 2016).…”
Section: Ethnic-racial Typicalitymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has found that those who appear more typical of their ingroup are more likely to experience outgroup discrimination (Maddox, 2004) and are perceived as more likely to be accepted among their ingroup (Wilson, 2021). Furthermore, previous studies have indicated that felt typicality among ethnic-racial minoritized persons was positively related to self-esteem and well-being (Hoffmann et al, 2020;Mitchell et al, 2018;Wilson & Leaper, 2016).…”
Section: Ethnic-racial Typicalitymentioning
confidence: 99%
“…Ingroup marginalization describes a within-group system of prejudice that stems from and mirrors processes of privilege and exclusion traditionally observed with outgroup discrimination. It can be based on various factors including adherence to perceived group norms for behavior, language, speech styles, and phenotypic appearance or skin tone (Bergin & Cooks, 2002;Fordham & Ogbu, 1986;Hunter, 1998;Maddox, 2004;Uzogara, 2019;Wilson, 2021). It is important to note that we are not equating the societal structures that perpetuate outgroup racist discrimination with the processes underlying ingroup marginalization.…”
Section: Ethnic-racial Outgroup Discrimination and Ingroup Marginaliz...mentioning
confidence: 99%
See 1 more Smart Citation